2019
DOI: 10.1002/cre2.182
|View full text |Cite
|
Sign up to set email alerts
|

A randomised bite force study assessing two currently marketed denture adhesive products compared with no‐adhesive control

Abstract: Unlike other oral care products, there are limited technologies in the denture adhesive category with the majority based on polymethyl vinyl ether/maleic anhydride (PVM/MA) polymer. Carbomer‐based denture adhesives are less well studied, and there are few clinical studies directly comparing performance of denture adhesives based on different technologies. This single‐centre, randomised, three‐treatment, three‐period, examiner‐blind, crossover study compared a carbomer‐based denture adhesive (Test adhesive) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…More participants in the no adhesive groups also reported multiple (>1) dislodgements. This is in agreement with previous studies examining the maximum incisal bite force a person can exert until denture dislodgement, which generally shows that a greater bite force is achievable when denture adhesive is used compared to no adhesive use (Axe et al, 2018 ; Jose et al, 2018 ; Varghese et al, 2019 ). Fewer denture dislodgements with the use of denture adhesive may be related to reduced movement of the denture while chewing (Tarbet et al, 1980 ) and supports the reduction in peanut particle infiltration observed in the primary analysis (Munoz et al, 2012 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…More participants in the no adhesive groups also reported multiple (>1) dislodgements. This is in agreement with previous studies examining the maximum incisal bite force a person can exert until denture dislodgement, which generally shows that a greater bite force is achievable when denture adhesive is used compared to no adhesive use (Axe et al, 2018 ; Jose et al, 2018 ; Varghese et al, 2019 ). Fewer denture dislodgements with the use of denture adhesive may be related to reduced movement of the denture while chewing (Tarbet et al, 1980 ) and supports the reduction in peanut particle infiltration observed in the primary analysis (Munoz et al, 2012 ).…”
Section: Discussionsupporting
confidence: 92%
“…Denture adhesives can improve these factors by creating a seal along the inner, gum‐facing denture borders. This can help improve denture fit, increase retentive hold (Hoke et al, 2017 ; Papadiochou et al, 2015 ), and reduce denture movement while chewing, which can, as a result, help with mastication and reduce infiltration of potentially irritating food particles under the denture (Axe et al, 2018 ; Gosavi et al, 2013 ; Kumar et al, 2015 ; Ozcan et al, 2005 ; Papadiochou et al, 2015 ; Varghese et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of differences between the different products investigated in this study might potentially facilitate a broader selection for consumers, allowing them to choose a denture adhesive based on personal preference and product availability. This broader range of options could potentially enhance acceptance and utilization among individuals who wear complete dentures [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maximum bite force [MBF] is a significant variable to evaluate oral function (5) .It additionally impacts diet selection, which has a vital role in the maintenance of masticatory activity (6)(7) . Old age people with missing teeth avoid a fibrous diet, which is considered an essential source of fibers, proteins, and vitamins (8)(9) .…”
Section: Introductionmentioning
confidence: 99%